(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: There are three objectives in this study; 1) to measure the live weight of pre-and post-weaning Saanen kids; 2) to determine the growth curves between males and females pre-and post-weaning Saanen kids; and 3) to analyze the body condition score (BCS) between male and female pre-and post-weaning kids. Materials and Methods: This study included pre-weaning kids aged 1 month, as well as post-weaning kids aged 3–6 months. 10 pre-weaning purebred Saanen kids (n = 5 male and n = 5 female) and 20 post-weaning Saanen kids (n = 10 male and n = 10 female) were employed in this investigation. Pre-and post-weaning kids’ live weights were assessed weekly on a weighing scale, and BCS was calculated based on their body frame. In the data analysis, the two-sample t-test with Minitab Software was utilized. Results: The findings revealed that pre-weaning Saanen kids gained weight steadily from week 1 to week 6, with males being heavier than females. The p-value, on the other hand, suggested that there was no difference in live weight between pre-weaning male and female Saanen kids. Over 6 weeks of sampling, the male had a larger proportion of live weight gain (80%) than the female (75%). Meanwhile, the BCS of pre-weaning Saanen kids grew from week 1 to week 6. It is critical to account for the development of muscle mass while still evaluating the fat cover to determine whether the kids are maintaining an adequate BCS. However, the live weight of post-weaning kids was inconsequential because they were still in the growing phase. As a result, from the 1st to 6th week, post-weaning kids’ body weight and BCS increased as their growth progressed. After 6 weeks of sampling, females had a higher percentage of live weight than males. This is because the kids raised on the farm do not have complete control over the environmental effects. Over 6 weeks of sampling, female post-weaning Saanen kids grew a slightly higher percentage of live weight (88%) than males (85%). Conclusion: This study conducted a direct assessment study, which monitored and determined the live weight and BCS of pre-and post-weaning Saanen kids. Pre-weaning kids’ average values of live weight were calculated as insignificant at the age of 1 month. The mean live weight is most affected by milk consumption from its mothers, the management of the farm, and the environment. For the post-weaning Saanen kids, the females have a slightly higher average live weight gained for 6 weeks than the males (p > 0.05). In conclusion, the live weight changes of Saanen kids during the weaning stages are independent of the BCS. J. Adv. Vet. Anim. Res., 9(3): 527–535, September 2022 http://doi.org/10.5455/javar.2022.i622